The assessment in the awareness regarding nutrition in pregnancy in population attending Dhiraj hospital and effect of taboos, customs and food availability on such population - Patwa, Khushboo N.; Kathrani, Sulay R.; Agrawal, Rushabh H.; Anand, Rakesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Food taboos have great effect on pregnant women through prohibited essential food and/or drinks. It is transferred from generation to generation and has negative effect on pregnant mothers’ health. The objective was to assess magnitude of food taboo and associated factors among pregnant women attending antenatal care at Dhiraj hospital, Waghodiya, Vadodara. Methods: Institutional based cross-sectional study was conducted. 180 pregnant women were selected for the study. Multiple logistic regression analysis was conducted to identify independent predictors of food taboo. Results: Twenty-seven percent of pregnant mother encountered food taboos. Avoided food items by pregnant mothers were linseed, coffee, tea, cabbage, meat, wheat bread, banana, groundnut, salty diet, sugarcane, pumpkin, and coca drinks. Reasons mentioned for avoidance of this food items were plastered on the fetal head, making fatty baby which is difficult for delivery, fear of abortion, and fetal abnormality. Age of the mother AOR=2.97 (1.71-5.16), income AOR=0.28 (0.11-0.72), and previous antenatal care AOR=2.33 (1.89-5.47) were significantly associated with food taboo. Conclusions: Our study revealed that considerable proportion of food taboo exists during pregnancy in the study area. This can be improved by strengthening the nutrition counselling components of antenatal care follow-up.